Dysregulated chaperones associated with cell proliferation and negative apoptosis regulation in the uterine leiomyoma. - Ura, Blendi; Scrimin, Federica; Arrigoni, Giorgio; Aloisio, Michelangelo; Monasta, Lorenzo; Ricci, Giuseppe (Oncol Lett, 2018)
Uterine leiomyomas are benign smooth muscle cell tumors that originate from the myometrium. In this study we focus on dysregulated chaperones associated with cell proliferation and apoptosis. Paired tissue samples of 15 leiomyomas and adjacent myometria were obtained and analyzed by two-dimensional gel electrophoresis (2-DE). Mass spectrometry was used for protein identification and western blotting for 2-DE data validation. The values of 6 chaperones were found to be significantly different in the leiomyoma when compared with the myometrium. A total of 4 proteins were upregulated in the leiomyoma and 2 proteins were downregulated. Calreticulin and 78 kDa glucose-regulated protein were further validated by western blotting because the first is considered a marker of cell proliferation, while the second protects against apoptotic cell death. In addition, we also validated the two downregulated proteins heat shock protein β-1 and heat shock 70 kDa protein 1A. Our study shows the existence of a dysregulation of chaperone proteins associated with leiomyoma development. Functional studies are needed to ascertain the role of these chaperones in the leiomyoma. This may be crucial for the further development of specific inhibitors against the activity of these proteins in order to block the growth of the leiomyoma.